Knowledge of patient's method of payment by physicians in a group practice. - Broida, J H (1975)
Physicians generally know how patients pay for their medical care. At the Marshfield Clinic, however, a group practice in Marshfield, Wis., physicians did not know the source of payment for the vast majority of their patients (79.3 percent). Also, even for the approximately one-fifth of the patients whose payment status they reported knowing, the information was incorrect for a small proportion. The patient's age and sex, length of time the physician had provided care, patient's place of employment, reason for patient's visit, and whether the physician was in the medical or surgical department apparently affected the physician's knowledge of the patient's payment status. Twenty-five of the 49 physicians studied reported they knew the payment status of none of their patients about whom they were asked; 24 knew the status of at least one patient. Only one physician in seven, however, reported having this knowledge about all the patients about whom he was asked. Physicians in medicine were more likely than those in surgical sub-specialties to know the patient's payment status. About one physician in five said such knowledge would be helpful for at least one patient; about one in seven said it would be helpful for all patients about whom they were asked. The Marshfield Clinic physicians, who receive salaries, emphasize comprehensive care and increased access to care, rather than maximization of income. The clinic offers medical care to patients in a prepayment health plan while continuing to serve other patients on a fee-for-service basis. Arrangements like this may help ease the transition to repayment if health-maintenance organizations become predominant in the delivery of health services in the United States.